Shape and count of free graphite particles in thin wall ductile iron castings - Borrajo, Juan Manuel (2002)
Recently, the scientific community has begun to study in detail the potential application of ductile iron in the production of thin wall components. Efforts are focused on the identification of the operative conditions necessary to obtain parts free of defects, with the desired microstructure. These aspects have been widely examined in the past for parts of conventional thickness (more than 5 mm), either experimentally or by using computational programs to model the solidification process. Nevertheless, modeling of thin walled parts is still unreliable, since specific databases are not available. The objective of this work is to study the evolution of the graphite nodule count and shape in ductile iron, as the section thickness diminishes down to 1.5 mm, using conventional casting procedures and resin bonded sand molds. A reasonably accurate correlation between solidification time and nodule count has been developed, based on experimental and modeled cooling curves. The morphology of graphite nodules has been characterized by image analysis, and the results correlated with the solidification time. The advantages of using solidification time as a parameter instead of thickness are also discussed.